José Bergamín : a critical introduction, 1920-1936 - Dennis, Nigel, 1949- (University of Toronto romance series, 1986)
This study sets out to explain the nature of the relationship José Bergamín (1895-1983) had as a critic and prose writer with the major poets of the 1920s and 1930s, and at the same time systematically examines the singularity of his own work as an aphorist, essayist, and dramatist.